A FeCoNiCrAl high entropy alloy reinforced copper-based surface composite material and preparation method thereof

By combining plasma spraying and friction stir processing, the complex problem of the reinforced material filling process in the prior art is solved, and the efficient preparation of FeCoNiCrAl high-entropy alloy reinforced copper-based surface composite material is achieved, with high strength and good wear resistance.

CN116377443BActive Publication Date: 2025-04-08CHANGCHUN UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310384045.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-12
Publication Date
2025-04-08
Estimated Expiration
2043-04-12

AI Technical Summary

Technical Problem

The existing friction stir processing methods are complex when filling reinforcement materials, resulting in waste of raw materials and increased time costs, and uneven distribution of reinforcement materials.

Method used

Plasma spraying is used to spray FeCoNiCrAl high-entropy alloy particles on the surface of the copper substrate to form a coating, and then friction stir processing is carried out to achieve uniform distribution of the reinforcement material.

Benefits of technology

The process flow is simplified, raw materials and time costs are saved, and the prepared composite materials have high strength and good wear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116377443B_ABST
    Figure CN116377443B_ABST
Patent Text Reader

Abstract

The invention discloses a FeCoNiCrAl high entropy alloy reinforced copper-based surface composite material and a preparation method thereof. A pure copper material is used as a substrate, and a FeCoNiCrAl high entropy alloy is used as a reinforcing material. The FeCoNiCrAl high entropy alloy is sprayed on the surface of the substrate by a plasma spraying device to form a coating with controllable thickness, and then the substrate and the high entropy alloy coating on the surface thereof are subjected to stir friction processing to obtain a FeCoNiCrAl high entropy alloy reinforced copper-based surface composite material. The method of combining plasma spraying and stir friction processing adopted by the invention solves the technical problem of the complex process flow of filling reinforcing materials when adopting the traditional stir friction processing method, simplifies the processing process, is simple to operate, is highly efficient, greatly saves the cost of raw materials and time cost, and the prepared composite material has fine grains, and the strength and wear resistance are significantly improved. The invention provides a new method for preparing a copper-based composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper-based composite material preparation, and relates to a FeCoNiCrAl high-entropy alloy reinforced copper-based surface composite material and a preparation method thereof. Background Art

[0002] Pure copper has high thermal conductivity, electrical conductivity, corrosion resistance, and easy processing and forming, and is considered one of the most effective metals in industry. However, the limitations of pure copper, such as poor ductility, low hardness, and poor wear resistance, have also largely inhibited its application.

[0003] In recent years, high entropy alloys have developed rapidly. They are alloys composed of 5 or more main elements in equal molar ratios (or nearly equal molar ratios). High entropy alloys have ultra-high strength and ductility, good thermal stability and high-temperature mechanical properties, high wear resistance and high corrosion resistance. At the same time, compared with ceramic reinforcements, high entropy alloys and metal matrices show good interface bonding and excellent compatibility in physical metallurgy, so high entropy alloys are an ideal reinforcement material for composite materials.

[0004] Friction stir processing has gradually developed into an advanced material surface processing technology with the advantages of easy operation, low cost, and less adverse interface reactions. In the preparation of composite materials, this processing method causes severe plastic deformation of the substrate, which is conducive to promoting the grain refinement of the substrate and the uniform distribution of the reinforcement material, and the distribution state of the reinforcement material can be further improved by controlling the processing passes. Therefore, friction stir processing has a wide range of uses in the preparation of composite materials.

[0005] However, at present, the filling of reinforcing materials during stir friction processing usually adopts two methods: grooving method and blind hole method. Both methods require cutting of the substrate, and the cutting standards are strict, resulting in a large waste of raw materials and increased time costs. Summary of the invention

[0006] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a method for preparing a FeCoNiCrAl high entropy alloy reinforced copper-based surface composite material. The preparation method is simple, and the prepared composite material has high strength and surface wear resistance.

[0007] In order to achieve the above-mentioned purpose, the present invention is realized through the following technical scheme: a preparation method of a FeCoNiCrAl high entropy alloy reinforced copper-based surface composite material, which takes pure copper material as a substrate and FeCoNiCrAl high entropy alloy particles as a reinforcing material, sprays the FeCoNiCrAl high entropy alloy particles on the surface of the substrate by plasma spraying equipment to form a coating, and then stirs and friction processes the substrate with the surface covered with the FeCoNiCrAl high entropy alloy coating to obtain the FeCoNiCrAl high entropy alloy reinforced copper-based surface composite material.

[0008] The method specifically comprises the following steps:

[0009] Step (1): pretreating the surface of the pure copper substrate;

[0010] Step (2): using a plasma spraying device to spray FeCoNiCrAl high entropy alloy particles onto the surface of a pure copper substrate to form a coating;

[0011] Step (3): The composite material with the FeCoNiCrAl high entropy alloy particle coating obtained in step (2) is subjected to friction stir processing along a bow-shaped zigzag path, wherein the path covers the entire high entropy alloy coating surface.

[0012] Preferably, in step (1), the surface of the pure copper substrate is pre-treated by sandblasting using a sandblasting machine and then ultrasonically cleaned.

[0013] The substrate used in step (1) is a copper plate with a purity of not less than 99.8%.

[0014] The particle size of the FeCoNiCrAl high entropy alloy particles in step (2) is 15 to 53 microns.

[0015] The parameters of plasma spraying in step (2) are as follows: spraying voltage is 50-60 V, spraying current is 550-650 A, main gas pressure is 60-70 PSI, carrier gas pressure is 55-60 PSI, spraying distance is 90 mm, and spraying speed is 350-400 mm / min.

[0016] The coating thickness formed in step (2) is 200 to 400 microns.

[0017] The interval of the bow-shaped fold lines in step (3) is determined by the shoulder diameter of the stirring needle and the overlap rate of adjacent welds, wherein the overlap rate of adjacent welds in the stir friction processing is 10% to 20%.

[0018] The parameters of the friction stir processing in step (3) are as follows: the rotation speed of the stirring head is 600-1000 r / min, the forward speed of the stirring head is 25-40 mm / min, the inclination angle of the stirring head is 2.5°, and the downward pressure is 0.5 mm.

[0019] In the step (3), the length of the stirring needle on the stirring head is selected within the range of 25% to 100% of the thickness of the composite material, the top diameter of the stirring needle is 3 mm, the bottom diameter is 5 mm, and the shoulder diameter of the stirring head is 16 to 20 mm.

[0020] The beneficial effects of the present invention are as follows:

[0021] The present invention realizes the preparation of FeCoNiCrAl high entropy alloy reinforced copper-based surface composite material by a method combining plasma spraying and stir friction processing. The method is simple to operate and has high efficiency. It solves the technical problem of complicated process flow of filling reinforcement materials when adopting traditional stir friction processing method, and greatly saves raw material cost and time cost. The prepared composite material has fine grains and uniform distribution of reinforcement materials. Compared with the original pure copper substrate, the hardness and wear resistance are significantly improved. In addition, the content of reinforcement materials in the composite material prepared by the method can be controlled by changing the coating thickness formed by plasma spraying to meet different requirements in actual production applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Schematic diagram of preparing FeCoNiCrAl high entropy alloy coating by plasma spraying according to the present invention;

[0023] Figure 2 Schematic diagram of preparing FeCoNiCrAl high entropy alloy reinforced copper-based surface composite material by friction stir processing of the present invention;

[0024] Figure 3 It is a schematic structural diagram of the FeCoNiCrAl high entropy alloy reinforced copper-based surface composite material of the present invention;

[0025] Figure 4 This is a microstructure morphology of the FeCoNiCrAl high entropy alloy reinforced copper-based surface composite material prepared in Example 1 of the present invention;

[0026] Figure 5 This is a microstructure morphology of the FeCoNiCrAl high entropy alloy reinforced copper-based surface composite material prepared in Comparative Example 1 of the present invention;

[0027] Figure 6 This is a microstructure morphology of the FeCoNiCrAl high entropy alloy reinforced copper-based surface composite material prepared in Comparative Example 2 of the present invention;

[0028] In the figure: 1-pure copper plate, 2-plasma spraying equipment, 3-FeCoNiCrAl coating, 4-stirring head, 5-overlapping area. DETAILED DESCRIPTION

[0029] The present invention is described in detail below with reference to specific embodiments.

[0030] Example 1

[0031] A preparation method of a FeCoNiCrAl high entropy alloy reinforced copper-based surface composite material, comprising: taking a pure copper material as a substrate and taking FeCoNiCrAl high entropy alloy particles as a reinforcing material, spraying the FeCoNiCrAl high entropy alloy particles on the surface of the substrate by plasma spraying to form a coating with controllable thickness, and then performing stir friction processing on the pure copper substrate and the high entropy alloy coating on the surface to obtain the FeCoNiCrAl high entropy alloy reinforced copper-based surface composite material.

[0032] The specific steps are as follows:

[0033] (1) The surface of a pure copper plate 1 having a purity of 99.8% and a size of 300 mm×300 mm×4 mm was pre-treated by sandblasting with a sandblasting machine and then ultrasonically cleaned;

[0034] (2) spraying FeCoNiCrAl high entropy alloy particles onto the surface of the pure copper plate 1 using a plasma spraying device 2 to form a FeCoNiCrAl high entropy alloy coating 3;

[0035] The particle size of the FeCoNiCrAl high entropy alloy particles in step (2) is 15 to 53 microns; the plasma spraying parameter settings are: voltage is 55 V, current is 600 A, main gas pressure is 70 PSI, carrier gas pressure is 60 PSI, spraying distance is 90 mm, and spraying speed is 400 mm / min; the thickness of the formed coating is 200 microns.

[0036] (3) The FeCoNiCrAl high entropy alloy coating of a certain thickness obtained in step (2) and its substrate are subjected to stir friction processing along a bow-shaped zigzag path to obtain a FeCoNiCrAl high entropy alloy reinforced copper-based surface composite material.

[0037] The bow-shaped fold line path in step (3) covers the entire high-entropy alloy coating surface, and the starting point and end point of the path are set at the edge of the pure copper substrate; the stirring head shoulder diameter selected for the stir friction processing is 16 mm, the stirring needle length is 2 mm, the stirring needle top surface diameter is 3 mm, the bottom surface diameter is 5 mm, the overlap rate of adjacent welds is 10%, and the interval of the bow-shaped fold line is 14.4 mm; the parameter settings of the stir friction processing are: the stirring head rotation speed is 900 r / min, the stirring head forward speed is 35 mm / min, the stirring head inclination angle is 2.5°, and the downward pressure is 0.5 mm.

[0038] This example successfully prepared a 4mm thick FeCoNiCrAl high entropy alloy reinforced copper-based surface composite material. The surface layer is a 2mm FeCoNiCrAl / Cu composite material layer, and the matrix is ​​a pure copper plate. Figure 4 As shown in Table 1, in the composite material, the FeCoNiCrAl particles are evenly distributed in the Cu matrix, the FeCoNiCrAl particles are tightly combined with the matrix, and there is no obvious gap at the interface. As shown in Table 1, the average hardness value of the material surface is 130.6HV, and the wear rate is 1.23×10 -6 g / N·m. The average hardness of the pure copper substrate surface is 84.5HV, and the wear rate is 2.23×10 -6 g 3 / N·m, compared with the pure copper substrate, the surface hardness and wear resistance of the composite material are significantly improved.

[0039] Example 2

[0040] The difference between this embodiment and embodiment 1 is that the plasma spraying parameters in step 2 are set as follows: voltage is 60V, current is 650A, and spraying speed is 360mm / min.

[0041] As shown in Table 1, the average hardness of the composite material surface prepared in this embodiment is 125.5 HV, and the wear rate is 1.46×10 -6 g / N·m.

[0042] Example 3

[0043] The difference between this embodiment and embodiment 1 is that the parameter settings of the friction stir processing in step 3 are: the rotation speed of the stirring head is 750 r / min, and the forward speed of the stirring head is 25 mm / min.

[0044] As shown in Table 1, the average hardness of the composite material surface prepared in this embodiment is 124.6 HV, and the wear rate is 1.55×10 -6 g / N·m.

[0045] Comparative Example 1

[0046] The difference between this comparative example and Example 1 is that the plasma spraying parameters in step 2 are set as follows: voltage is 80 V, current is 750 A, and spraying speed is 400 mm / min.

[0047] Figure 5 The microstructure morphology of the composite material prepared in Comparative Example 1. As shown in Table 1, the average hardness of the surface of the composite material prepared in this comparative example is 96.7 HV, and the wear rate is 2.01×10 -6 g / N·m.

[0048] Comparative Example 2

[0049] The difference between this comparative example and Example 1 is that the parameter settings of the friction stir processing in step 3 are: the rotation speed of the stirring head is 1200 r / min, and the forward speed of the stirring head is 25 mm / min.

[0050] Figure 6 The microstructure morphology of the composite material prepared in Comparative Example 2. As shown in Table 1, the average hardness of the surface of the composite material prepared in this comparative example is 98.4 HV, and the wear rate is 1.91×10 -6 g / N·m.

[0051] pass Figure 4 , Figure 5 and Figure 6 It can be seen from the comparison that the microstructure uniformity of the composite material prepared by using the process parameters beyond the range of the present invention is far less than that of Example 1. As shown in Table 1, the average hardness value and wear resistance of Examples 1-3 are significantly higher than those of Comparative Examples 1 and 2, indicating that the plasma spraying parameter setting and the stir friction processing parameter setting have a great influence on the performance of the composite material.

[0052] The present invention uses pure copper as a matrix material and FeCoNiCrAl high entropy alloy as a reinforcement material, and combines plasma spraying and stir friction processing to prepare a FeCoNiCrAl high entropy alloy reinforced copper-based surface composite material. The method is simple to operate, efficient, and controllable in composition. It solves the technical problem of complex process flow of filling reinforcement materials when using traditional stir friction processing methods, and greatly saves raw material costs and time costs. The prepared composite material reinforcement particles are evenly distributed, and compared with the original pure copper substrate, the hardness and wear resistance are significantly improved. In addition, the content of reinforcement particles in the composite material prepared by the method can be controlled by changing the coating thickness formed by plasma spraying to meet different requirements in actual production applications.

[0053] Table 1 shows the test results of the average hardness and wear rate of the composite materials prepared in Examples 1-3 and Comparative Examples 1 and 2 of the present invention.

[0054] Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Average hardness value / HV 130.6 125.5 124.6 96.7 98.4 Wear rate / g / N·m <![CDATA[1.23×10 -6 ]]> <![CDATA[1.46×10 -6 ]]> <![CDATA[1.55×10 -6 ]]> <![CDATA[2.01×10 -6 ]]> <![CDATA[1.91×10 -6 ]]>

[0055] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the scope of implementation of the present invention. Therefore, all equivalent changes made to the contents described in the claims of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a FeCoNiCrAl high entropy alloy reinforced copper-based surface composite material, characterized in that: The method specifically comprises the following steps: Step (1): pretreating the surface of a pure copper substrate; the thickness of the pure copper substrate is not less than 4 mm; Step (2): using a plasma spraying device to spray FeCoNiCrAl high entropy alloy particles onto the surface of a pure copper substrate to form a coating; the thickness of the coating is in the range of 200 to 400 μm; The parameter settings of the plasma spraying equipment are as follows: the spraying voltage is 50~60V, the spraying current is 550~650A, the main gas pressure is 60~70 PSI, the carrier gas pressure is 55~60 PSI, the spraying distance is 90 mm, and the spraying speed is 350~400mm / min; Step (3): the composite material with the FeCoNiCrAl high entropy alloy particle coating obtained in step (2) is subjected to friction stir processing along a bow-shaped zigzag path, wherein the path covers the entire high entropy alloy coating surface; the length of the stirring needle on the stirring head is selected within a range of 25% to 100% of the thickness of the composite material; The parameter settings of the friction stir processing are as follows: the rotation speed of the stirring head is 600~1000 r / min, the forward speed of the stirring head is 25~40mm / min, the inclination angle of the stirring head is 2.5°, and the downward pressure is 0.5mm.

2. The method for preparing the FeCoNiCrAl high entropy alloy reinforced copper-based surface composite material according to claim 1, characterized in that: Step (1): Pre-treat the surface of the pure copper substrate by sandblasting with a sandblasting machine and perform ultrasonic cleaning.

3. The method for preparing the FeCoNiCrAl high entropy alloy reinforced copper-based surface composite material according to claim 1, characterized in that: In step (1), the pure copper substrate is a copper plate with a purity of not less than 99.8%.

4. The method for preparing the FeCoNiCrAl high entropy alloy reinforced copper-based surface composite material according to claim 1, characterized in that: The particle size of the FeCoNiCrAl high entropy alloy particles in step (2) is 15 to 53 microns.

5. The method for preparing the FeCoNiCrAl high entropy alloy reinforced copper-based surface composite material according to claim 1, characterized in that: The interval of the bow-shaped fold lines in step (3) is determined by the shoulder diameter of the stirring needle and the overlap rate of adjacent welds, wherein the overlap rate of adjacent welds in the stir friction processing is 10% to 20%.

6. A FeCoNiCrAl high entropy alloy reinforced copper-based surface composite material prepared by the method according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Preparation method of high-speed steel wear-resistant layer on aluminum alloy surface

    CN102284786A

  • Wide-temperature-domain lubricant and abrasion-resistant composite coating and preparation and spraying methods thereof

    CN111349881A

  • High-entropy-alloy-based self-lubricating composite and preparation method thereof

    CN111575698A

  • Application of friction stir processing method in refining magnesium alloy structure

    CN114289856A